Optimasi Perencanaan Produksi Kerupuk Bawang Fajar Menggunakan Metode Goal Programming - Refina Rintani; Arnellis Arnellis; Dony Permana (UNIVERSITAS NEGERI PADANG, 2018)
Abstract – This study discusses the optimization of production planning . Optimation is done by using goal programming method on the product of Kerupuk Bawang Fajar in Indarung Padang. Problems that occur in this business is less optimal implementation of onion cracker production. The production process is not through careful planning. So often the excess of raw materials. This research’s purpose is to know the model for production planning and to know the result of production planning optimization on Kerupuk Bawang Fajar by using goal programming method. The form of goal programming model is an extension of linear programming, it’s just there are deviasional variables on the function constraints that serve to accommodate the deviation of the completion of the goal to be achieved. The optimal production of Kerupuk Bawang Fajar is the original garlic cracker as much as 792 packs / day, spicy onion cracker as much as 130 packs / day, carrot flavor cracker as much as 151 packs / day, potato garlic crackers as much as 130 packs / day, and purple sweet potato crackers as much as 90 packs / day. With profit maximization of Rp. 12.167.291 and a minimization costs of Rp 3.373.378.